Hubungan Antara Kecerdasan Emosional dan Kepercayaan Diri dengan Kemandirian Belajar Siswa di SMP Negeri 9 Tebing Tinggi - Liany Rosa Indah Dalimunthe; Syaiful Akhyar Lubis; Azhar Aziz (Universitas Medan Area, 2019)
Learning independence is one of the whips to face the challenges and learning tasks faced. Independent students can complete their work or tasks well even without the help of others. The purpose of this study to determine the relationship between emotional intelligence and confidence with student learning independence in SMP Negeri 9 Tebing Tinggi. The population of this study are students of SMP Negeri 9 Tebing Tinggi as many as 600 students with random sampling technique obtained a sample of 120 respondents. Data analysis technique using multiple regression analysis technique. The result of the research shows that emotional intelligence and students' self-reliance in Junior High School 9 Tebing Tinggi are in normal category, while the self confidence of students of SMP Negeri 9 Tebing Tinggi is high. From the results of the first hypothesis test showed that there is a positive and significant relationship between emotional intelligence with learning independence with a correlation of 0.606 and p-value 0.000. The second hypothesis shows that there is a positive and significant relationship between self-confidence with learning independence with a correlation of 0.565 and p-value 0.000. Furthermore, the third hypothesis shows that there is a positive and significant relationship between emotional intelligence and confidence with learning independence with a correlation of 0.706 and p-value 0.000. The total effective contribution of emotional intelligence and self confidence variables with student learning independence in SMP Negeri 9 Tebing Tinggi is 70.6%.